Facilitating groupwork in an extended scope placement - Bryan, Samantha; Marshall, Elizabeth (Groupwork, 2017)
Abstract: This article discusses the opportunity of new and emerging roles within the Occupational Therapy profession within a non-traditional setting, including a charity run organisation. The article identifies how the unique skills of an Occupational Therapist, such as activity analysis, grading and adapting environments, enables individuals to regain a missed role in life/skill or acquire a new one. This reflective account draws upon the experiences of two 2nd year Occupational Therapy students facilitating a reminiscent occupation focussed intervention on a scope placement. There is an emphasis on how meaningful occupations can enhance mental health are examined. Analysis of group work is investigated, challenges faced, drawing parallels to Belbin’s team-work roles. Qualitative outcomes are discussed that measure the effectiveness of group work within this elderly localised population and provide a baseline of which future research would be beneficial. To conclude - The outcome of this reflective account highlights the importance of gaining a deeper understanding of group work and the dynamics considered to do this effectively. This applies to collaborative practice amongst teams but also when engaging individuals to be less isolated, as part of an intervention of therapy. Clinical practice, reflections, and relevant literature provide the student with the tools of self-development, enabling better quality service user experience. The experience accounted, shows reflective evidence that Occupational Therapists can encompass all the benefits of group work alongside an therapeutic intervention to bring value to an individuals’ t social and physical wellbeing Keywords: groupwork; group work; occupational therapy,; student; reminiscence; baking; intervention